Bound state effects in transverse momentum parton distributions - Maintas, X. N.; Diakonos, F. K.; Galanopoulos, G. D.; Kaplis, N. K.; Papoulias, C. I.; Tsagkarakis, H. E. (HNPS Advances in Nuclear Physics, 2020)
We use a non-gaussian intrinsic transverse momentum distribution, associated with the wavefunction of the partonic ground state inside the proton, to calculate the production of π0 with intermediate transverse momentum values in p − p collisions at high energies. It is shown that a perfect description of the experimental data for different experiments is achieved using an almost constant value for the mean transverse momentum of the initial partons, compatible with Heisenberg’s uncertainty relation (⟨kT ⟩ ≈ 0.3 GeV ). Our analysis suggests the presence of a non-vanishing, non-perturbative contribution from partonic bound states to the pp → πo(γ) + X and pp → p + X cross section.